KAJIAN KOMPARATIF PRODUKTIVITAS DAN PROFITABILITAS USAHATANI PADI KONVENSIONAL DENGAN ORGANIK DI KECAMATAN KALIGONDANG KABUPATEN PURBALINGGA - Utami, Dewanti Risa; Zulkifli, Lutfi; Rachmah, Malinda Aptika (AGROTEKSOS; Vol 36 No 2 (2026): Jurnal Agroteksos Agustus 2026, 2026)
Organic rice has become an alternative to conventional rice, which is now widely consumed by the general public. The trend toward healthy living has led to an increase in demand for organic rice, especially since the selling price of this product in the market is higher than that of conventional rice. This is also the case in Kaligondang Subdistrict, Purbalingga Regency, where several farmers grow rice organically and are even certified, namely in Penolih Village. However, problems arise when organic certification expires, causing farmers to return to conventional farming methods. The purpose of this study is to determine the comparison of productivity and profitability levels of rice farming in conventional and organic cultivation systems to identify other conditions that may cause the failure to switch from conventional to organic rice cultivation, with a sample size of 41 rice farmers who cultivate rice using conventional and organic systems. The results of the study show that the productivity and profitability of conventional farming are higher than those of organic farming, with a difference of 18.28 kw/ha and 36%. This was reinforced by the results of the significance test, which showed a significant difference in productivity levels ranging from 968.59 to 2,687.55 and a range of 20.45% to 51.55% for the t-test of profitability, which showed a consistent difference between conventional and organic rice farming. Further research is needed, ranging from cultivation techniques to market access, supported by the government and relevant institutions, if farmers are to switch to organic farming systems again.